Social responsibility of Muslim youth towards the challenges of the modern world - Rahath House, Yousef (2014)
The purpose of this Keynote speech is to emphasise the importance of social vision of Islam in formulating Islamic identity of Muslim youth. It has been assumed that due to the negligence of social dimension of Islam, most of the contemporary Islamic youth organisations are incapable of enabling the younger generation to look at the historical context of their lived reality more critically. Consequently, majority of the Muslims are not bothered about several concrete human social problems such as inequality, economic exploitation and fragmentation of the community into different classes and groups. To solve this issue, the speech suggests incorporation of social dimension of Islam when youths formulate their world view. Since the Quran portrays human being as a social being by highlighting his various responsibilities in this world, one of the guiding principles of Islamic activities should be to make Muslims capable of understanding the world for making it more just and better. Only then would Muslims be able to make a link between the faith and social action.